CRISPR-Cas knockout of miR21 reduces glioma growth - Nieland, Lisa; Solinge, Thomas S. van; Cheah, Pike See; Morsett, Liza M.; Khoury, Joseph El; Rissman, Joseph I.; Kleinstiver, Benjamin P.; Broekman, Marike L. D.; Breakefield, Xandra O.; Abels, Erik R. (Cell Press, 2022)
Non-coding RNAs, including microRNAs (miRNAs), support the progression of glioma. miR-21 is a small, non-coding transcript involved in regulating gene expression in multiple cellular pathways, including the regulation of proliferation. High expression of miR-21 has been shown to be a major driver of glioma growth. Manipulating the expression of miRNAs is a novel strategy in the development of therapeutics in cancer. In this study we aimed to target miR-21. Using CRISPR genome-editing technology, we disrupted the miR-21 coding sequences in glioma cells. Depletion of this miRNA resulted in the upregulation of many downstream miR-21 target mRNAs involved in proliferation. Phenotypically, CRISPR-edited glioma cells showed reduced migration, invasion, and proliferation in vitro. In immunocompetent mouse models, miR-21 knockout tumors showed reduced growth resulting in an increased overall survival. In summary, we show that by knocking out a key miRNA in glioma, these cells have decreased proliferation capacity both in vitro and in vivo. Overall, we identified miR-21 as a potential target for CRISPR-based therapeutics in glioma.